2002
DOI: 10.2320/matertrans.43.1283
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Twinning in Boron-Doped Ni<SUB>3</SUB>Al

Abstract: Dependence of frequency of annealing twinning events on annealing temperature and composition, especially boron content, in polycrystalline Ni 3 Al alloys has been investigated by means of optical and transmission electron microscopy, and also by evaluation of coherent twin boundary energy via counting the wrong atomic bonds across twin boundaries. Microstructural observation found that after homogenization at temperatures from 1000 to 1360 • C both binary and boron-doped Ni 3 Al alloys without prestrain show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…6 are not violated in the range of the first and second nearest neighbors [20,36]. However, the wrong atomic bonds across twin boundary are present if the atomic bonds exceeding the second and halfnearest neighbors are taken into account [34,36]. For example, there exist three excess A-A wrong bonds and one excess B-B wrong bond at second and half-nearest neighbor, and also six deficit A-A wrong bonds and six deficit A-B wrong bonds at third nearest neighbor.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…6 are not violated in the range of the first and second nearest neighbors [20,36]. However, the wrong atomic bonds across twin boundary are present if the atomic bonds exceeding the second and halfnearest neighbors are taken into account [34,36]. For example, there exist three excess A-A wrong bonds and one excess B-B wrong bond at second and half-nearest neighbor, and also six deficit A-A wrong bonds and six deficit A-B wrong bonds at third nearest neighbor.…”
Section: Discussionmentioning
confidence: 95%
“…Among possible two types of twin boundaries (i.e., complex stacking fault (CSF)-type and superlattice stacking fault (SISF)-type twin boundaries) shown in Fig. 6, the SISF-type twin boundary has been suggested to be stable (i.e., have the least energy) in L1 2 ordered structure because it does not involve wrong bonds in the first and second neighbors across twin boundary [20,34]. Based on this result, it has been suggested that the γ SFE (or γ twin ) of the stable (i.e., SISF-type) twin boundary for the L1 2 (A 3 B)-type ordered alloy can primarily be estimated as that of the major components, i.e., A atoms; consequently, it was deduced that the γ SFE for the Co 3 Ti and Ni 3 (Si,Ti) alloys is close to that of fcc Co-based alloys, e.g.…”
Section: Discussionmentioning
confidence: 98%
“…However, the values of γ SF for the Co 3 Ti and Ni 3 (Si,Ti) alloys are not available at the present time. In the previous paper [11], the value of γ SF for the Co 3 Ti and Ni 3 (Si,Ti) ordered alloys was estimated in terms of energetic and geometrical consideration for twin boundaries in L1 2 ordered structure, as follows; between possible two-types of twin boundaries (i.e., complex stacking fault (CSF)-type and superlattice stacking fault (SISF)-type twin boundaries), the SISF-type twin boundary has been suggested to be stable (i.e., have the least energy) in L1 2 ordered structure because it does not involve wrong bonds in the first and second neighbors across twin boundary [11,12]. Therefore, it has been suggested that the γ SF (or γ twin ) of the stable (i.e., SISF-type) twin boundary for the L1 2 (A 3 B)-type ordered alloy can primarily be estimated as that of the major components, i.e., A atoms.…”
Section: Discussionmentioning
confidence: 99%